181k views
0 votes
5(3x+4)-2x =7x-3(2x+11) and7x-(3x+5)-8=(1/2)*(8x+20)-7x+5find x in each of the expression

User Wrdieter
by
4.8k points

1 Answer

4 votes

i) x = -53/12

ii) x = 4

Step-by-step explanation:

i) 5(3x+4) - 2x =7x - 3(2x+11)

expand the parenthesis:

15x + 20 - 2x = 7x - 6x - 33

15x - 2x + 20 = 7x - 6x - 33

13x + 20 = x - 33

collect like terms:

13x - x = -33 - 20

12x = -53

divide both sides by 12:

x = -53/12

ii) 7x - (3x+5) -8 =(1/2)*(8x+20) -7x+5​

7x - 3x - 5 - 8 = 8x/2 + 20/2 - 7x + 5

4x - 13 = 4x + 10 -7x + 5

4x - 13 = -3x + 15

collect like terms:

4x + 3x = 15 + 13

7x = 28

x = 28/7

x = 4

User RbG
by
4.5k points